Compass needle in inhomogeneous magnetic field

We consider a cylindrical coil of length l = 40 cm , l = 40\, \text{cm}, radius R = 4 cm , R = 4 \, \text{cm}, and number of turns N = 3200. N = 3200. A constant electric current I = 4 A I = 4 \, \text{A} flows through the coil, so that a magnetic field B \vec B is created. Now we place a small compass inside the coil at z = 1 2 l z = - \frac{1}{2} l . The compass needle is aligned along the magnetic field and has a magnetic moment of μ = 0.1 J / T \mu = 0.1 \, \text {J} / \text {T} .

What is the absolute value of the force F \vec F exerted by the magnetic field on the compass needle?

Details: Along the z z -axis, the magnetic field of the cylindrical coil results in B ( z ) = μ 0 N I 2 l [ z + l 2 R 2 + ( z + l 2 ) 2 z l 2 R 2 + ( z l 2 ) 2 ] e z , \vec B(z) = \frac{\mu_0 N I}{2 l} \left[ \frac{z + \frac{l}2}{\sqrt{R^2 + \left(z + \frac{l}2\right)^2}} - \frac{z - \frac{l}2}{\sqrt{R^2 + \left(z - \frac{l}2\right)^2}} \right] \vec e_z, where μ 0 = 4 π 1 0 7 N / A 2 \mu_0 = 4 \pi \cdot 10^{-7} \,\text{N}/\text{A}^2 is the vacuum permeability

F 5 1 0 6 N F \approx 5 \cdot 10^{-6}\,\text{N} F 5 1 0 4 N F \approx 5 \cdot 10^{-4} \,\text{N} F 5 1 0 2 N F \approx 5 \cdot 10^{-2} \,\text{N} F 5 N F \approx 5 \,\text{N} F 5 1 0 2 N F \approx 5 \cdot 10^2 \,\text{N} The magnetic field exerts a pure torque on the compass needle so that F = 0 F = 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Inside the magnetic field of the coil, the compass needle has a potential energy E pot E_\text{pot} , that is given by the dot product of the magnetic moment μ \vec \mu and the magnetic field B \vec B : E pot = μ B ( z ) = μ B ( z ) = z F ( z ) d z E_\text{pot} = - \vec \mu \cdot \vec B(z) = - \mu B(z) = - \int_{-\infty}^z F(z') dz' where F ( z ) F(z) is the corresponding magnetic force. Differentiation after z z yields F ( z ) = μ d B d z = μ 0 μ N I 2 l d d z [ z + l / 2 R 2 + ( z + l / 2 ) 2 z l / 2 R 2 + ( z l / 2 ) 2 ] = μ 0 μ N I 2 l [ 1 R 2 + ( z + l / 2 ) 2 1 R 2 + ( z l / 2 ) 2 ( z + l / 2 ) 2 ( R 2 + ( z + l / 2 ) 2 ) 3 / 2 + ( z l / 2 ) 2 ( R 2 + ( z l / 2 ) 2 ) 3 / 2 ] = μ 0 μ N I 2 l [ R 2 ( R 2 + ( z + l / 2 ) 2 ) 3 / 2 R 2 ( R 2 + ( z l / 2 ) 2 ) 3 / 2 ] \begin{aligned} F(z) &= \mu \frac{dB}{dz} = \frac{\mu_0 \mu N I}{2 l} \frac{d}{dz}\left[ \frac{z + l/2}{\sqrt{R^2 + (z + l/2)^2}} - \frac{z - l/2}{\sqrt{R^2 + (z - l/2)^2}} \right] \\ &= \frac{\mu_0 \mu N I}{2 l} \left[ \frac{1}{\sqrt{R^2 + (z + l/2)^2}} - \frac{1}{\sqrt{R^2 + (z - l/2)^2}} - \frac{(z + l/2)^2}{(R^2 + (z + l/2)^2)^{3/2}} + \frac{(z - l/2)^2}{(R^2 + (z - l/2)^2)^{3/2}} \right]\\ &= \frac{\mu_0 \mu N I}{2 l} \left[ \frac{R^2}{(R^2 + (z + l/2)^2)^{3/2}} - \frac{R^2}{(R^2 + (z - l/2)^2)^{3/2}} \right] \end{aligned} Now we evaluate the force at z = l / 2 z = -l/2 : F ( l / 2 ) = μ 0 μ N I 2 l [ 1 R R 2 ( R 2 + l 2 ) 3 / 2 ] R l μ 0 μ N I 2 l [ 1 R R 2 l 3 ] R l μ 0 μ N I 2 l R = 4 π 1 0 7 0.1 3200 4 2 0.4 0.04 N 0.05 N \begin{aligned} F(-l/2) &= \frac{\mu_0 \mu N I}{2 l} \left[ \frac{1}{R} - \frac{R^2}{(R^2 + l^2)^{3/2}} \right] \\ & \stackrel{R \ll l}{\approx} \frac{\mu_0 \mu N I}{2 l} \left[ \frac{1}{R} - \frac{R^2}{l^3} \right] \\ & \stackrel{R \ll l}{\approx} \frac{\mu_0 \mu N I}{2 l R} \\ & = \frac{4 \pi \cdot 10^{-7} \cdot 0.1 \cdot 3200 \cdot 4}{2 \cdot 0.4 \cdot 0.04} \,\text{N} \\ &\approx 0.05 \,\text{N} \end{aligned} (The approximations are optional, but simplify the numerical evaluation)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...